Governance reform in Shenzhen 2013-2018: a case study - Mao, Dun (2020)
Based on the research of anti-corruption enforcement in Shenzhen, the ‘Demonstration City of Socialism with Chinese Characteristics’ of the People’s Republic of China, this thesis investigates the reasons behind the introduction of ‘governance’ into the Communist Party of China’s (CPC) vision of reform, as well as considering how this affects the way in which social and administrative concerns are managed. The first part of the thesis explores the different between ‘government’ and ‘governance’ mechanisms in China before moving on to discuss how governing mechanisms changed following the CPC’s adoption of ‘governance’. The thesis goes on to consider if the critical socio-political problems that China faces today could be solved by introducing the philosophy and mechanisms of governance and compares the effectiveness of this approach with more traditional methods. This study also presents an investigation of corruption and its management in China, before offering suggestions about how China could adapt governance mechanisms to maximise their effectiveness. This study found that several reforms in both the private and public sectors have been instigated as a result of adopting the CPC’s notion of governance. These findings were enabled through analysing and interpreting a range of sources, including official statistics, government documents and secondary literature, as well as fieldwork data that was carried out in Shenzhen. These reforms include the organisational structure of government, how laws are designed and enforced, operational approaches in the public sector and the notions of civil engagement and accountability. In addition, personnel management has been affected by the reforms, particularly the way that these employees are supervised and assessed. The research concludes that these reforms have contributed to a strengthening of China’s control over corruption.